2012
DOI: 10.2109/jcersj2.120.579
|View full text |Cite
|
Sign up to set email alerts
|

Salt-assisted solution combustion synthesis of ZnFe<sub>2</sub>O<sub>4</sub> nanoparticles and photocatalytic activity with TiO<sub>2</sub> (P25) as nanocomposite

Abstract: Well-dispersed zinc ferrite (ZnFe 2 O 4 ) nanoparticles were successfully prepared by a novel salt-assisted solution combustion process. The effects of types and amounts of the added salt on the properties of the products were investigated by XRD, SEM, and BET nitrogen adsorption techniques. The results indicated that the introduction of salt into reaction system facilitate the formation of well-dispersed spinel zinc ferrite and increase specific surface area of the resultants from 7.14 to 88.34 m 2 ·g ¹1 when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The addition of KCl reduces the crystal size and increases the surface area. The higher addition of KCl and NaCl in the synthesis of ZnFe 2 O 4 using the solution combustion method with L-α Alanine as fuel decreases the crystal size and increases the surface area [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of KCl reduces the crystal size and increases the surface area. The higher addition of KCl and NaCl in the synthesis of ZnFe 2 O 4 using the solution combustion method with L-α Alanine as fuel decreases the crystal size and increases the surface area [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The double bond fuel, such as urea (triple), are called unsaturated bonds and are generally more reactive. Therefore, the crystal formation process occurs quicker [ 26 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The LTO particles exhibit micro sizes ranging from 1.83 to 2.28 µm, and all samples display a cubic morphology with a smooth surface. Moreover, previous studies reported that at certain concentrations, salt can prevent the agglomeration of particles during the sintering process [37,38,54]. Based on SEM images, the agglomeration of LTO particles is occurred without the NaCl addition (Figure 2a).…”
Section: Morphology Analysis Of Ltomentioning
confidence: 79%
“…Zinc ferrite is synthesized by sol-gel auto-combustion [10], hydrothermal [11], co-precipitation [12] methods. TiO 2 /ZnFe 2 O 4 nanocomposites have been synthesized by sol gel [13], impregnation [5], hydrothermal [3] methods or grinding two components together [14]. In this study, microwave-assisted hydrothermal synthesis was extended to preparation of ZnFe 2 O 4 nanoparticles and ZnFe 2 O 4 /TiO 2 nanocomposite and their photocatalytic activity was determined using different light sources.…”
Section: Introductionmentioning
confidence: 99%